Pregabalin and Tranexamic Acid Evaluation by Two Simple and Sensitive Spectrophotometric Methods - Nawab Sher; Nasreen Fatima; Shahnaz Perveen; Farhan Ahmed Siddiqui; Alisha Wafa Sial (International Journal of Analytical Chemistry)
This paper demonstrates colorimetric visible spectrophotometric quantification methods for amino acid, namely, tranexamic acid and pregabalin. Both drugs contain the amino group, and when they are reacted with 2,4-dinitrophenol and 2,4,6-trinitrophenol, they give rise to yellow colored complexes showing absorption maximum at 418 nm and 425 nm, respectively, based on the Lewis acid base reaction. Detailed optimization process and stoichiometric studies were conducted along with investigation of thermodynamic features, that is, association constant and standard free energy changes. The method was linear over the concentration range of 0.02–200 µgmL−1 with correlation coefficient of more than 0.9990 in all of the cases. Limit of detection was in range from 0.0041 to 0.0094 µgmL−1 and limit of quantification was in the range from 0.0137 to 0.0302 µgmL−1. Excellent recovery in Placebo spiked samples indicated that there is no interference from common excipients. The analytical methods under proposal were successfully applied to determine tranexamic acid and pregabalin in commercial products. t-test and F ratio were evaluated without noticeable difference between the proposed and reference methods.